2019
DOI: 10.1111/jzo.12679
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of the hyoid apparatus in Jamaican fruit bats (Chiroptera: Phyllostomidae) in unraveling the evolution of echolocation in bats

Abstract: How echolocation and flight evolved in modern day bats is a compelling and largely unanswered question in biology. As laryngeal echolocation in bats is typified by a bony connection between the larynx and the auditory bulla via the hyoid apparatus, we developed an evolutionary‐developmental model of the hyoid to test hypotheses regarding the evolution of echolocation in bats. Using computed tomography of pre‐ and postnatal Jamaican fruit bats (Artibeus jamaicensis), we showed that much of the hyoid apparatus w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Hyoid morphology has been recognized as a key component of laryngeal echolocation [31,32,37,40,41,44,49,53,[77][78][79][80]. Regarding the entire morphology of the hyoid apparatus in bats, it has been suggested that the number of hyoid components varies among lineages [44].…”
Section: Implications For the Evolution Of The Laryngeal Echolocation...mentioning
confidence: 99%
“…Hyoid morphology has been recognized as a key component of laryngeal echolocation [31,32,37,40,41,44,49,53,[77][78][79][80]. Regarding the entire morphology of the hyoid apparatus in bats, it has been suggested that the number of hyoid components varies among lineages [44].…”
Section: Implications For the Evolution Of The Laryngeal Echolocation...mentioning
confidence: 99%
“…The pre-volant pups emitted echolocation regularly in response to nearby sounds as early as day 0, and in a preliminary test with a week old pup the individual responded to echolocation passes as well (electronic supplementary material, figure S3). In laryngeal bats, the drastic adjustment of vocal signals in the first month corresponds with morphological changes supporting the superfast musculature of the larynx, auditory sensitivity and audiovocal feedback [8,10,14,53,[55][56][57][58][59]. Laryngeal echolocating pups vary in their onset of hearing, but generally have lower auditory sensitivity than adults and hearing ranges restricted to lower frequencies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The ontogeny of the cochlea has been described as accelerated compared to non-echolocator mammals (Nojiri et al 2021b) and among bats, specific developments of the hearing apparatus have illuminated several evolutionary pathways (Nojiri et al 2021a). The ontogeny of the hyoid apparatus and the intrinsic laryngeal cartilages shows correlations with the development of echolocation, and the different echolocation strategies have been implicated in the reinforcement by mineralisation/ossification of some parts of the cartilages during postnatal development (Carter et al 2019;Carter 2020). Also, these correlations between echolocation strategies and reinforcement of the larynx coupled to the ontogenetic pathways illustrated in the development of bioacoustics indicate possible evolutionary scenarios.…”
Section: Evolutionary Development and Ontogenymentioning
confidence: 92%
“…In terms of anatomical research in the development of laryngeal echolocation, only a few research have been published regarding the relationship between anatomy and echolocation (e.g., Pedersen 1995;Nojiri et al 2021b). Some of that research considered the evolutionary aspect of laryngeal echolocation (e.g., Nojiri et al 2021a) and only the recent research in ontogeny focused on the laryngeal aspect of sound production and its implication in laryngeal echolocation development (e.g., Carter et al 2019;Carter 2020). These research highlighted that the ontogeny of the skull (Pedersen 1995) and of the cochlea (Carter and Adams 2016;Nojiri et al 2021b) illustrated some constraints by the demands of vocalisations in bats.…”
Section: Evolutionary Development and Ontogenymentioning
confidence: 99%